The Concept of Self-Boundaries to Reduce People-Pleaser in the Qur'an (Thematic Interpretation Analysis) - Shobibah Azzahro; Wiwin Ainis Rohtih; Amir Mahmud; M. Mukhid Mashuri (al-Afkar, Journal For Islamic Studies, 2026)
People pleaser behavior  is an individual's tendency to always please others at the expense of their own needs and interests. This phenomenon often arises due to social pressure, bullying experiences, demanding family parenting, and the need for social acceptance. These conditions can have an impact on mental health and loss of self-integrity. Therefore, the concept  of self-boundaries as a healthy self-boundary is needed as a solution so that individuals are able to maintain a balance between doing good to others and defending their own rights. This study aims to examine the conception of self-boundaries in the Qur'an as an effort to reduce the behavior of people pleasers. The research uses the library research method with a descriptiveanalytical approach and the maudhu'i (thematic) interpretation method. The primary data source is the Qur'an, while the secondary source includes books of tafsir such as Tafsir Al-Munir, Tafsir Al-Misbah, and Tafsir Ibn Kathir, as well as relevant psychological literature. The results of the study show that the Qur'an provides principles related to the formation of self-limits, including through an emphasis on sincerity of intention, personal responsibility, the prohibition of following social pressures without a basis in truth, and the encouragement to help in good without engaging in self-destructive deeds. Verses such as QS Al-Kahfi: 103–104, QS AlBaqarah: 195, QS Al-Maidah: 2, QS Al-Isra': 7, and QS Al-Muddatstsir: 38 shows that man must maintain the orientation of charity to the pleasure of Allah and be responsible for his own deeds. Thus, the concept  of self-boundaries in the perspective of the Qur'an can be the basis for building a person with integrity, able to socialize healthily, and not trapped in people pleaser behavior.